2021
DOI: 10.1172/jci.insight.146883
|View full text |Cite
|
Sign up to set email alerts
|

Highly multiplexed 2-dimensional imaging mass cytometry analysis of HBV-infected liver

Abstract: Studies of human hepatitis B virus (HBV) immune pathogenesis is hampered by limited access to liver tissues and technologies for detailed analyses. Here, utilizing imaging mass cytometry (IMC) to simultaneously detect 30 immune, viral and structural markers in liver biopsies from patients with HBeAg + chronic hepatitis B, we provide novel comprehensive visualization, quantitation and phenotypic characterizations of hepatic adaptive and innate immune subsets that correlated with hepatocellular injury, histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Other researchers(28) investigated immune-related changes in the aged liver and found that the levels of in ammatory cytokines, chemokines, and in ammatory genes were higher in aged animals. The latest results (29) (30). Thus, age-associated changes in intrahepatic immune subsets appear trivial in ACLF patients, and we did not nd that recipient age affects the therapeutic effects of UCMSCs in the ACLF group.…”
Section: Discussionmentioning
confidence: 63%
“…Other researchers(28) investigated immune-related changes in the aged liver and found that the levels of in ammatory cytokines, chemokines, and in ammatory genes were higher in aged animals. The latest results (29) (30). Thus, age-associated changes in intrahepatic immune subsets appear trivial in ACLF patients, and we did not nd that recipient age affects the therapeutic effects of UCMSCs in the ACLF group.…”
Section: Discussionmentioning
confidence: 63%
“…Other researchers [ 28 ] investigated immune-related changes in the aged liver and found that the levels of inflammatory cytokines, chemokines, and inflammatory genes were higher in aged animals. The latest results [ 29 ] revealed that older age was associated with increased hepatic accumulation of Kupffer and CD11b+ cells, as well as with adaptive immune activation and clinical evolution in chronic hepatitis B associated with age-associated changes in intrahepatic immune subsets. In this study, we mainly focused on whether the effects of UCMSCs on patients with HBV-related acute-on-chronic liver failure and liver cirrhosis were affected by recipient age.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of activated CD8 T cells is a hallmark of HBV-associated liver damage in CHB patients (Maini et al, 2000;Traum et al, 2021), but our understanding of their role in viral hepatitis has relied largely on animal models. Longitudinal human liver sampling with core biopsies is impractical and invasive.…”
Section: Discussionmentioning
confidence: 99%